Formulation and Characterization of Soursop Leaf extract (Annona muricata L.) Nanoemulsion Using VCO and Tween 80 - Ratih Dyah Puspitasari; Desfira Sarani; Dina Erliana; Munifilia Ekasari (KOVALEN: Jurnal Riset Kimia, 2025)
Methanol extract of soursop leaves contains various bioactive compounds such as alkaloids, saponins, tannins, and flavonoids. To increase the absorption of these compounds, a nanoemulsion formulation of soursop leaf extract was carried out. Extraction was carried out using the maceration method using 96% methanol, followed by a thickening process using a rotary evaporator and freeze drying to obtain the dry extract. The nanoemulsion preparation was made from methanol extract of soursop leaves (Annona muricata L.) using Virgin Coconut Oil (VCO) as the oil phase and Tween 80 as a surfactant. The nanoemulsion was formulated using a high-energy method using an ultrasonicator. Two formulas were tested (F1 and F2) and evaluated through organoleptic tests, clarity (transmittance), physical stability (centrifugation), solubility, emulsion type, storage test (freeze-thaw), and measurement of droplet size and polydispersity index with a Particle Size Analyzer (PSA). The results showed that formula F1 had the most optimal characteristics, with a clarity of 80% indicating better droplet dispersion with an average droplet size of 13.96 nm and a polydispersity index of 0.216 indicating the successful formation of a stable and uniform nanoemulsion. Nanoemulsions showed good physical stability, were soluble in polar and semi-polar solvents, and were oil-in-water (O/W) type supporting increased solubility and availability of active compounds in air-based systems. These results indicate that F1 is the most potential formula to increase the bioavailability of active compounds in soursop leaves and can be further developed as a carrier system candidate in pharmaceutical preparations.